Remote sensing and buoy based monitoring of chlorophyll a in the Yangtze Estuary reveals nutrient-limited status dynamics: A case study of typhoon - Xu, Yuying; Chen, Jianyu (Frontiers in Marine Science, 2022)
Nutrient concentrations and its limited statuses can affect phytoplankton community structure and marine primary productivity. Identifying limiting nutrients under different ocean conditions, the causes, and the nature of such limitations, has important implications for understanding ecosystem changes and interpretation of in situ data. However, there is still a lack of retrieval methods for nutrients in seawater, especially in coastal waters. We propose to characterize the spatiotemporal variability of phytoplankton and nutrient-limited status in the surface ocean with diurnal valuevs of chlorophyll concentration. In this paper, the sediment fronts and plume fronts are used as a reference to select the relative and absolute nutrient-limited status regions. The variance of the six times per day (9:30-14:30) is calculated to represent the diurnal variation of chlorophyll, and the diurnal variation and concentration of chlorophyll combined are used to analyze nutrient-limited status. The results indicate that the diurnal variation of chlorophyll is greater after the typhoon, and the nutrient-limited status is different following each typhoon passing by. The in situ data shows that the highest chlorophyll a concentration reached 20.7 mg/m3 after the typhoon in August 2011.